Qualidade informacional dos lucros: influência de investidores sofisticados no Brasil. - Passos, Lineker Costa (2017)
The research aims to examine whether investors demand for useful and efficient information affects firms' managers decisions to report earnings with required information attributes in the context of Brazilian capital market. Persistence of accruals - measured according Dechow and Dichev (2002) model, modified by McNichols (2002) - and asymmetric economic losses recognition timeliness practice - estimated according Ball and Shivakumar (2005) to the model of - were the quality attributes of earnings information. Investors’ informational demand was proxy by relevant institutional investors (representing sophisticated financiers) shareholder base participation, as well as their attendance in company's boards. Data collection proceed on Economática® database and in BM&FBovespa and CVM portals by Reference Forms (FR), Annual Information (IAN) and AGO and AGE Board of Directors Meeting appraisals. The period includes 1998 to 2015 data. For empirical inferences were processed descriptive statistics, mean tests, correlation analyses and multiple regression analyses. Coefficients and parameters were estimated by GMM-SYS (Generalized Method of Moments - System) in order to mitigate variables omission and endogeneity questions. Findings indicated that institutional investors - considered as sophisticated investors - exert earnings quality effective demand in Brazilian market, influencing accruals persistence and conditional conservatism in published financial statements. The degree of such influence changes according to different investors’ category, to the kind of participation in the companies and the continuity in the condition like shareholder in the firms. These findings conduct to not reject the hypothesis that informational efficiency of disclosed earnings in Brazilian capital market experiences marginal and positive influence of sophisticated investors demand.